Fire and ice - Hunter, Erin. (New York : Avon, 2004)
Fireheart, a full-fledged warrior cat, must confront questions of loyalty and identity as he faces the possibility of betrayal from within his own forest clan.
6.8
5-8
Keywords: Cats -- Fiction; Fantasy; Cats -- Fiction; Fantasy fiction